Q-switched hafnium bismuth erbium-doped fiber laser with bismuth (III) telluride based saturable absorber - Zakaria, U.N.; Harun, Sulaiman Wadi; Reddy, Pinninty Harshavardhan; Dutta, Debjit; Das, Shyamal; Dhar, Anirban; Paul, Mukul Chandra; Jusoh, Zulzilawati; Yasin, Moh (National Institute R and D of Materials Physics, 2018)
In this work, we fabricated the Bismuth (III) Telluride (Bi2Te3) based saturable absorber (SA) by embedding the material into polyvinyl Alcohol (PVA) film. By incorporating the film inside laser cavity with a homemade Hafnium Bismuth Erbium-doped fiber (HBEDF) as a gain medium, a stable Q-switched fiber laser was generated to operate at 1532 nm region. The repetition rate of the laser was tunable from 41.1 to 61.0 kHz while corresponding pulse width shrinks from 9.46 to 5.48 µs as the 980 nm pump power rises from 69 to 122 mW. The maximum pulse energy was 31.5 nJ. To the best of our knowledge, this is the first report on the Q-switched fiber laser using n relatively short length of HBEDF as the gain medium.